Implementation of Model Reference Adaptive Controller with Fractional Order Adjustment Rules for Coaxial Rotor Control Test System - Kavuran, G.; Alagoz, B B; Ateş, A.; Yeroğlu, C. (My University, 2016)
— In this study, an experimental test platform of a low-cost coaxial rotors has been developed for implementation of Model Reference Adaptive Controller (MRAC) with Fractional Order Adjustment Rules by using MATLAB/Simulink. This paper provides a design method of MRAC with fractional order adjustment rule (FOAR-MRAC) that is implemented on a hardware based on ARM microcontroller. Setup of the test platform is presented and its performance is evaluated with realtime experimental measurements. This experimental study is useful to show the utilization of fractional order control systems on engineering applications by using low-cost hardware
Keywords: Mühendislik; Elektrik ve Elektronik